MODIFIED MARICHAYADI TAILYA (MMT) IN THE MANAGEMENT OF PRATISHAYA (RHINITIS)- A MULTI DIMENSIONAL STUDIES - Gopal C Nanda,; Debashree Priyadarshini,; Binodini Tripathy, (International Journal of Ayurveda and Pharma Research, 2021)
Rhinitis is a very common and complicating disease condition usually affects more than 90% of the population varying from simple sneezing to multiple complications along with frequency. Usually, it affects due to pollution further follower by bacterial infection in naso-pharyngeal track. Most often it is managed instantly with anti-allergic medications like nasal drop and tablet, syrup, etc. but due to suppression of condition for a longer period it remains dormant causing multiple complications in future. Looking to the condition a nasal drop prepared from few herbs processed with mustard oil was taken into multiple clinical- experimental trial both invivo and invitro study to access the efficacy. The nasal drop in the form of Nasya i.e., modified Marichyadi taila (MMT) in management of Pratishyaya (rhinitis) has been evaluated from different angle i.e., clinical, radiological, biochemical, biological and antibiogram study etc. show significant result in comparison with modern control drug Otrivin. After comparing both the results it has found that MMT was more effective than Otrivin as because of its multi-stained bactericidal and virucidal effect along with maximum relief in clinical sign and symptoms. It was also observed that the drug is effective from 48-72hrs and to be continued for one to two weeks for optimum relief. Efforts have been taken to highlight the specific findings pertaining to different study in the present paper.